Insights into the effect of solvent on dibenzothiophene hydrodesulfurization. (1st March 2021) - Wang, Bo; Zheng, Peng; Fan, Huili; Meng, Qian; Duan, Aijun; Chen, Zhentao; Xu, Chunming
Graphical abstract: Highlights: Solvent affects the overall TOF and HDS reaction network. Vaporization of DBT and diffusion resistance reduce HDS rate in liquid phase system. Competitive adsorption has significant effects on DBT HDS and its network. H2 donation of tetralin has negative effects since producing polycyclic aromatics. Abstract: The hydrodesulfurization (HDS) of dibenzothiophene (DBT) over a NiMo/Al-SBA-15 catalyst was performed in different solvent systems and the results showed that the solvent selection had a great impact on the TOF values and the reaction networks. The phase equilibrium experiments, and the PRO/II stimulation ascribed the solvent effects as the partial evaporation of DBT and the large diffusion resistance in the gas-liquid-solid reaction. The density functional theory (DFT) simulation and the GC–MS results attributed the solvent effects to the competitive adsorption of H2, DBT, and the solvent molecules on the active sites. Hydrogen donations of decalin and tetralin were found to have negligible contributions to the HDS processes, while the corresponding dehydrogenation process of decalin and tetralin would produce naphthalene and the other polycyclic aromatic compounds, consequently leading to the lower HDS efficiencies. Furthermore, the internal diffusion effectiveness factors ( η ) were calculated, and the results demonstrated that the HDS of DBT in the p-xylene and tetralin solvent systems were limited by the surface-reactions, while that in the DBT-cyclohexane system was limited by the intraparticle diffusion.